Risques naturels, aléas, vulnérabilités: le cas de la ville de Praia sur l’île de Santiago (Cap-Vert) - Monteiro, Sílvia (2016)
The small archipelago of Cape Verde, for its volcanic origin and its location in the context of the sahelian climate suffers the effects of a tumultuous and violent nature, with big hazards (volcanism, droughts, floods, landslides, erosion). These phenomena are hardly experienced by a very vulnerable population, located on a discontinuous territory with very poor infrastructure. A strong urbanization of the population did grow the city of Praia, which is the capital of the country, and the city extends today spontaneously and disorderly. The occupation of floodplains and unstable slopes by neighborhoods spontaneous poses a lot of problems in terms of hazards. The poor quality of many houses, the fragility of the materials used and the low economic power of residents increase the vulnerability of these areas face the risk event. In this article, we examine the main natural hazards in Cape Verde and in its capital, the city of Praia, trying to contribute to a better management of the urban territory.